2019
DOI: 10.3390/su11246984
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Decision for Reverse Logistics System under Cross-Competitive Take-Back Mode Based on Game Theory

Abstract: Considering the reverse logistics system composed of two manufacturers and two recyclers under the cross-competitive take-back mode, which is influenced by multiple factors (industry competition, economies of scale, government subsidies, remanufacturing rate, etc.), a model for remanufacturing reverse logistics system based on Stackelberg game is established. Then, the Nash equilibrium solution of decision variables is solved to obtain the best profit of all participants under the cross-competitive take-back m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Huang and Wang [31] explored three types of take-back models in a hybrid remanufacturing system, manufacturer's take-back, distributor's take-back, and third-party's take-back, and showed that all the received profits of supply chain members from the take-back activities are even larger than those from non-take-back activities. Feng et al [32] considered the cross-competitive take-back mode in a CLSC consisting of two manufacturers and found that cross-competitive take-back is even more beneficial to all supply chain members than monopolistic take-back. Pazoki and Samarghandi [33] and Chang et al [34] investigated how take-back regulations imposed by the government encourage remanufacturing or eco-design.…”
Section: Clscs With a Take-back Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Huang and Wang [31] explored three types of take-back models in a hybrid remanufacturing system, manufacturer's take-back, distributor's take-back, and third-party's take-back, and showed that all the received profits of supply chain members from the take-back activities are even larger than those from non-take-back activities. Feng et al [32] considered the cross-competitive take-back mode in a CLSC consisting of two manufacturers and found that cross-competitive take-back is even more beneficial to all supply chain members than monopolistic take-back. Pazoki and Samarghandi [33] and Chang et al [34] investigated how take-back regulations imposed by the government encourage remanufacturing or eco-design.…”
Section: Clscs With a Take-back Activitymentioning
confidence: 99%
“…Refs. [28,29,[31][32][33][34][35] focused on take-back activities in CLSCs but did not consider coalition strategies. With increasing concerns about the sustainable operation of supply chains, devising the optimal coalition strategies is indeed a universally significant task for supply chain members.…”
Section: Research Gaps and Contributionsmentioning
confidence: 99%
“…Reviews, evaluation studies, and game theory are found in seven papers. Interestingly, the authors of all seven game-theory-model papers [60,[64][65][66][67][68][69] 2 presents the categorizations of all 87 papers based on research subjects and methodologies adopted by authors. The survey-based methodology is the most prominent one adopted by most authors, with 21 papers, followed by mathematical modeling papers, with 9 papers.…”
Section: Research Subjectsmentioning
confidence: 99%
“…Reviews, evaluation studies, and game theory are found in seven papers. Interestingly, the authors of all seven game-theory-model papers [60,[64][65][66][67][68][69] are based in China. Table 4 presents the concentration of research fields pursued by the authors.…”
Section: Research Subjectsmentioning
confidence: 99%
“…There are many formal institutions operating WEEE chains in Brazil, including cooperatives, logistics companies and recyclers (CEMPRE 2020). RL can generate economic and social bene ts, enabling the emergence of new businesses, generating work and income (SOUZA et al 2015;FENG et al 2019; SAHAJWALLA; HOSSAIN 2020). It is worth emphasizing the importance of studies that provide decisionmakers with effective information and tools for the analysis and optimization of RL scenarios (RODRIGUES; MONDELLI 2021).…”
Section: Weee Reverse Logistics In Brazilmentioning
confidence: 99%